2013
DOI: 10.21608/jpp.2013.74230
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF IRRIGATION LEVELS, ANTITRANSPIRANTS AND POTASSIUM SILICATE ON GROWTH, FRUIT YIELD AND QUALITY OF SWEET PEPPER PLANTS (Capsicum annuum L.) GROWN UNDER DRIP IRRIGATION

Abstract: Two field experiments were conducted at a private farm near EL-Mansoura city, El-Dakahlia Governorate, Egypt, during the two successive seasons of 2011 and 2012 to study the effect of three water irrigation levels, the first was 2600 m 3 fed -1 as the control treatment (the traditional irrigation amount used by the farmers in the area), the 2 nd and the 3 rd treatments were 1800 and 1000 m 3 fed -1 , respectively, as deficit irrigation treatments as well as four foliar applications, i.e., control, magnesium ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
6
11
0
Order By: Relevance
“…The application with glycine -betaine was the best in number of fruits/plant, average fruit weight, yield/fed .Followed by glutathione or potassium silicate in the two seasons, respectively .The same trend was appeared in fruit physical characters table 7. Similar results were obtained by Mäkelä et al (1998) on tomato , Sakr et al (2015) and (Kamal, 2013) on pepper respectively.…”
Section: Effect Of Foliar Applicationsupporting
confidence: 87%
“…The application with glycine -betaine was the best in number of fruits/plant, average fruit weight, yield/fed .Followed by glutathione or potassium silicate in the two seasons, respectively .The same trend was appeared in fruit physical characters table 7. Similar results were obtained by Mäkelä et al (1998) on tomato , Sakr et al (2015) and (Kamal, 2013) on pepper respectively.…”
Section: Effect Of Foliar Applicationsupporting
confidence: 87%
“…The positive effect of spraying antitranspirants materials on seed yield of squash plants that achieved in our study may be attributed to the increased vegetative growth parameters, i.e, fresh and dry weights, plant length, No. of leaves and leaf area, and chemical constituents in leaves, i.e, N, P and K percentage as well as total chlorophyll (a+b) and leaves proline content, as previously shown in Tables 2 & 3. The obtained results are supported by the findings of Wafaa (2002); Kuruppaiah et al (2003); Al-Omran et al (2005); Ibrahim and Selim (2010);El-Afifi et al (2013); Kamal (2013) and Ramadan and Omar (2017).…”
Section: Effect Of the Interactionssupporting
confidence: 84%
“…Spraying squash plants by kaolin 2% and MgCO 3 2% under irrigation with 80% from ETc gave better results than untreated plants under irrigation with 100% from ETc .These results are supported by the findings of El-Afifi et al (2013) and Kamal (2013) who showed a significant superiority of adding kaolin on the N,P,K percentage in eggplant and bell pepper leaves.…”
Section: Effect Of Interactions Between Irrigation Water Treatments Asupporting
confidence: 70%
“…Foliar spray with potassium silicate increased plant growth, and yield and its components on strawberries (Wand and Galletta 1998), bean (Abou-Baker et al, 2011), sweet pepper (Kamal, 2013) Therefore, the aim of this work was to determin suitable planting date and potassium silicate rate to obtain high growth and best productivity of two garlic cultivars under clay soil and using flood irrigation system. http:/www.journals.zu.edu.eg/journalDisplay.aspx?Journalld=1&queryType=Master…”
Section: Introductionmentioning
confidence: 99%